Design and In-silico Molecular Docking of NMDA NR2B Receptor Antagonist and Pharmacokinetic Prediction of Some Piperazine Sulfonyl Amine Derivatives for Alzheimer’s Disease: Pharmaceutical Science-Pharmaceutical chemistry - Kumar, Sachin; Prabahar, A. Elphine; Sharma, Rajesh Kumar (International Journal of Life Science and Pharma Research, 2022)
Alzheimer’s disease is a rare and progressive neurologic disease caused by degeneration of neurons within the brain that causes the brain to shrink (atrophy) and brain cells to die. In the US, approximately 5.5 million people are affected, and the prevalence worldwide is estimated to be as high as 24 million. Treatment is available to reduce the symptoms but no permanent cure. NMDA receptors play a crucial role in the treatment of Alzheimer’s. Our aim and objective of the present work are to design some piperazine sulfonyl amine derivatives for treating Alzheimer’s disease. To achieve this objective, we have docked the designed ligands with NMDA receptors. In our study, we have designed some piperazine sulfonyl amine derivatives, which were then subjected to virtual screening. The three-dimensional crystal structure of the selected protein NMDA receptor subunit NR2B (PDB Id: 3JPW) was retrieved from the RCSB Protein Data Bank (PDB). The ligands that showed low binding energy were further predicted for pharmacokinetic properties, and Lipinski’s rule of 5 and the results are discussed. The final 19 compounds were used to develop a pharmacophore. The finalized 19 compounds were subjected to various in silico screening processes like drug-likeness, ADME properties and toxicity prediction. All 19 compounds exhibited good draggability nature, while ligands SE-B-15 and SE-B-12 were carcinogenic and SE-E-2 and SE-E-13 were prone to cause immunotoxicity. Ligands SE – C – 13 and SE – B – 2 exhibited good docking scores and best pharmacokinetic properties.